Pollution of Coastal Aquifers: A Human Induced Environmental Hazards, Visakhapatnam Area, Andhra Pradesh, India - A Remote sensing and G.I.S. approach - M. Ganesh, K; Jai Sankar, G; Jagannadha Rao, M; Rambabu, T (International Journal of Engineering and Technology, 2018)
Groundwater forms very little quantity when compared to the total water available on the earth. Therefore it is very vital for all living beings especially for human consumption. Visakhapatnam is one of the fastest growing Coastal cities in India with rapid development of industrial and urban activity. The present study has been carried out to evaluate the Coastal aquifer Pollution and City area Ground water pollution using GIS. Thematic layers have been generated from Ground water quality data and available ancillary data, i.e. for index overlay operations for identification of groundwater pollution zones in the study area using statistical method of point data interpolation and GIS.Â Â